The concise Oxford companion to classical literature (Oxford Univ. Pr., 1993)
Derived from the highly praised second edition of The Oxford Companion to Classical Literature, this is the ideal reference book for anyone interested in the classical world and its literary heritage. Including accounts of the lives and works of the classical authors, character entries and plot summaries, general entries tracing the development of literary forms such as comedy and tragedy, and wide coverage of the historical, political social, and artistic background of ancient works, The Concise Oxford Companion to Classical Literature is indispensable for readers of classical literature, and equally accessible to anyone wishing simply to trace an allusion or understand the inspiration behind so much of Western art. Comprehensive and completely accessible, The Concise Oxford Companion to Classical Literature includes accounts of the lives and works of the classical authors; character entries and plot summaries; general entries tracing the development of the various literary forms; extensive coverage of the historical, political, social, and artistic background; and translation of all Greek and Latin words.